ΑΝΤΙ ΠΡΟΛΟΓΟΥ: ΟΙ ΚΟΙΝΟΤΗΤΕΣ ΤΗΣ ΕΛΛΗΝΙΚΗΣ ΧΕΡΣΟΝΗΣΟΥ ΚΑΤΑ ΤΗΝ ΤΟΥΡΚΟΚΡΑΤΙΑ. ΜΙΑ ΑΠΟΠΕΙΡΑ ΣΧΗΜΑΤΙΚΗΣ ΚΑΤΑΤΑΞΗΣ ΣΤΟΝ ΧΩΡΟ, ΚΑΤΑ ΤΗΝ ΕΣΩΤΕΡΙΚΗ ΟΙΚΟΝΟΜΙΚΗ ΚΑΙ ΠΟΛΙΤΙΚΗ ΤΟΥΣ ΛΕΙΤΟΥΡΓΙΑ - ΕΥΘΥΜΙΟΥ, ΜΑΡΙΑ (Eoa kai Esperia, 2007)
During the centuries of Ottoman Rule the local communities of the GreekPeninsula had to fulfill basic duties towards the Ottoman State. This madethem create a local political life more or less rich and complicated, dependingon their geographical position and local circumstances. Some of the biggercommunities of the zone northern than the Volos - Farsala - Arta line,presented -mostly due to their proximity with the dense net of the CentralBalkan roads and ports of commerce- a vivid political life, in whichparticipated the local merchants and artisans with their guilds as well as thelocal religious and administrative clerks and leaders. On the contrary, to thesouth of the above mentioned zone (in Central Greece, in Peloponnesus andin most of the small islands of the Aegean) the local communal political lifewas less complicated, and in the hands of persons or institutions whose localpower was more connected to the land than to handicraft and commerce.